Engineering of Escherichia coli for Krebs cycle-dependent production of malic acid - Trichez, Debora (Microb Cell Fact, 2018)
BACKGROUND: Malate is a C4-dicarboxylic acid widely used as an acidulant in the food and beverage industry. Rational engineering has been performed in the past for the development of microbial strains capable of efficient production of this metabolite. However, as malate can be a precursor for specialty chemicals, such as 2,4-dihydroxybutyric acid, that require additional cofactors NADP(H) and ATP, we set out to reengineer Escherichia coli for Krebs cycle-dependent production of malic acid that can satisfy these requirements. RESULTS: We found that significant malate production required at least simultaneous deletion of all malic enzymes and dehydrogenases, and concomitant expression of a malate-insensitive PEP carboxylase. Metabolic flux analysis using (13)C-labeled glucose indicated that malate-producing strains had a very high flux over the glyoxylate shunt with almost no flux passing through the isocitrate dehydrogenase reaction. The highest malate yield of 0.82 mol/mol was obtained with E. coli Δmdh Δmqo ΔmaeAB ΔiclR ΔarcA which expressed malate-insensitive PEP carboxylase Ppc(K620S) and NADH-insensitive citrate synthase GltA(R164L). We also showed that inactivation of the dicarboxylic acid transporter DcuA strongly reduced malate production arguing for a pivotal role of this permease in malate export. CONCLUSIONS: Since more NAD(P)H and ATP cofactors are generated in the Krebs cycle-dependent malate production when compared to pathways which depend on the function of anaplerotic PEP carboxylase or PEP carboxykinase enzymes, the engineered strain developed in this study can serve as a platform to increase biosynthesis of malate-derived metabolites such as 2,4-dihydroxybutyric acid. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12934-018-0959-y) contains supplementary material, which is available to authorized users.